Delayed presentation of superficial femoral pseudoaneurysm after closed treatment of femoral shaft fracture: A case report and review literature - Pattraluck Anantasinkul; Chittawee Jiamton (Journal of Orthopaedic Reports, 2025)
A superficial femoral artery aneurysm is a rare but potentially life- and limb-threatening complication. This case report describes a patient with a long spiral periprosthetic fracture of the right femur who developed a pseudoaneurysm of the superficial femoral artery following conservative treatment. The patient presented with thigh swelling, significant pain, and an unexplainable dropped in hematocrit level. Despite surgical fixation and vascular repair, the patient developed limb ischemia, necessitating an above-knee amputation. This case highlights the importance of vigilance for vascular complications in patients with femoral fractures, particularly involving a long spiral or oblique fracture of the distal shaft femur.